A responsabilidade civil da empresa na fase de prevenção e mitigação do ciclo dos desastres antropogênicos: um estudo do controle jurídico da atividade empresarial no Brasil - Heilbuth, Diogo Calazans Ferreira (2024)
This dissertation deals with the company's civil liability for creating the risk of a disaster. It analyzes the possibility of civil liability in the prevention and mitigation phase of the disaster cycle, when there is an opportunity to prevent the harmful event from occurring. In order to improve preventive legal control of business activity in Brazil, the research addresses the new field of study called disaster law, in the light of international guidelines on disasters and human rights that apply to business activity. It then looks at Brazilian domestic law and identifies challenges in the field of enforceability of rules that impose risk management and the implementation of measures to prevent damage and violations of rights. The analysis of the factual scenario that preceded the disaster in Brumadinho/MG helps to understand the legal consequences (in the administrative, civil and criminal spheres) caused by the risk of disaster. Finally, considering the importance of the preventive function of civil liability, the possibility of dispensing with damage as a prerequisite for the establishment of the institute is verified. It is also noted that contractual civil liability can also contribute, along with non-contractual liability, to preventive legal control of business activity, reducing the occurrence of anthropogenic disasters